The epigenetic impact of suberohydroxamic acid and 5‑Aza‑2'‑deoxycytidine on DNMT3B expression in myeloma cell lines differing in IL‑6 expression - Trtkova, Katerina Smesny; Luzna, Petra; Drozdkova, Denisa Weiser; Cizkova, Katerina; Janovska, Lucie; Gursky, Jan; Prukova, Dana; Frydrych, Ivo; Hajduch, Marian; Minarik, Jiri (Molecular medicine reports, 2022)
Gene inactivation of the cyclin‑dependent kinase inhibitors p16INK4a, p15INK4b and p21WAF is frequently mediated by promoter gene methylation, whereas histone deacetylases (HDACs) control gene expression through their ability to deacetylate proteins. The effect of suberohydroxamic acid (SBHA) and 5‑Aza‑2'‑deoxycytidine (Decitabine) (DAC) treatments on the transcription of CDKN2A, CDKN2B and CDKN1A genes, and their effects on molecular biological behavior were examined in two myeloma cell lines, RPMI8226 and U266, which differ in p53‑functionality and IL‑6 expression. In both tested myeloma cell lines, a non‑methylated state of the CDKN2B gene promoter region was detected with normal gene expression, and the same level of p15INK4b protein was detected by immunocytochemical staining. Furthermore, in myeloma cells treated with SBHA and DAC alone, the expression of both p15INK4b and p21WAF was significantly upregulated in RPMI8226 cells (p53‑functional, without IL‑6 expression), whereas in the U266 cell line (p53 deleted, expressing IL‑6) only p21WAF expression was significantly increased. Moreover, the analysis revealed that treatment with DAC induced DNMT3B enhancement in U266 cells. In conclusion, in myeloma cells with IL‑6 expression, significantly increased DNMT3B expression indicated the tumorigenic consequences of 5‑Aza‑2'deoxycytidine treatment, which requires careful use in diseases involving epigenetic dysregulation, such as multiple myeloma (MM).
Keywords: multiple myeloma cell lines; interleukin-6; proteiny buněčného cyklu; nádorové buněčné linie; DNA methylation; Cell Line, Tumor; Cell Cycle Proteins; lidé; Humans; Multiple Myeloma; inhibitor p15 cyklin-dependentní kinasy; DNA Methyltransferase 3B; Cyclin-Dependent Kinase Inhibitor p16; Cyclin-Dependent Kinase Inhibitor p15; metylace DNA; DNA-(cytosin-5-)methyltransferasa; mnohočetný myelom; nádorový supresorový protein p53; Interleukin-6; DNA-methyltransferasa 3B; epigeneze genetická; umlčování genů; DNA Methylation; interleukin‑6; DNA (Cytosine-5-)-Methyltransferases; Tumor Suppressor Protein p53; Decitabine; inhibitor p16 cyklin-dependentní kinasy; decitabin; Epigenesis, Genetic; Gene Silencing; cyclin‑dependent kinase inhibitor